Graphene–ferroelectric metadevices for nonvolatile memory and reconfigurable logic-gate operations - Woo Young Kim (Nature Portfolio, 2016)
Metamaterial memory devices often require a large stimulus to switch states or suffer from poor thermal stability. Here, the authors fabricate a terahertz metadevice driven by ferroelectric and graphene layers, and obtain multiple level memory devices stable at room temperature.